RETRACTED: The two-component system CpxR/A represses the expression of Salmonella virulence genes by affecting the stability of the transcriptional regulator HilD - De la Cruz, Miguel A.; Pérez-Morales, Deyanira; Palacios, Irene J.; Fernández-Mora, Marcos; Calva, Edmundo; Bustamante, Víctor H. (Frontiers in Microbiology, 2015)
Salmonella enterica can cause intestinal or systemic infections in humans and animals mainly by the presence of pathogenicity islands SPI-1 and SPI-2, containing 39 and 44 genes, respectively. The AraC-like regulator HilD positively controls the expression of the SPI-1 genes, as well as many other Salmonella virulence genes including those located in SPI-2. A previous report indicates that the two-component system CpxR/A regulates the SPI-1 genes: the absence of the sensor kinase CpxA, but not the absence of its cognate response regulator CpxR, reduces their expression. The presence and absence of cell envelope stress activates kinase and phosphatase activities of CpxA, respectively, which in turn controls the level of phosphorylated CpxR (CpxR-P). In this work, we further define the mechanism for the CpxR/A-mediated regulation of SPI-1 genes. The negative effect exerted by the absence of CpxA on the expression of SPI-1 genes was counteracted by the absence of CpxR or by the absence of the two enzymes, AckA and Pta, which render acetyl-phosphate that phosphorylates CpxR. Furthermore, overexpression of the lipoprotein NlpE, which activates CpxA kinase activity on CpxR, or overexpression of CpxR, repressed the expression of SPI-1 genes. Thus, our results provide several lines of evidence strongly supporting that the absence of CpxA leads to the phosphorylation of CpxR via the AckA/Pta enzymes, which represses both the SPI-1 and SPI-2 genes. Additionally, we show that in the absence of the Lon protease, which degrades HilD, the CpxR-P-mediated repression of the SPI-1 genes is mostly lost; moreover, we demonstrate that CpxR-P negatively affects the stability of HilD and thus decreases the expression of HilD-target genes, such as hilD itself and hilA, located in SPI-1. Our data further expand the insight on the different regulatory pathways for gene expression involving CpxR/A and on the complex regulatory network governing virulence in Salmonella.